Comparing Kadish, TNM, and the modified Dulguerov staging systems for esthesioneuroblastoma. Issue 1 (22nd November 2018) - Joshi, Rohan R.; Husain, Qasim; Roman, Benjamin R.; Cracchiolo, Jennifer; Yu, Yao; Tsai, Jillian; Kang, Julie; McBride, Sean; Lee, Nancy Y.; Morris, Luc; Ganly, Ian; Tabar, Viviane; et al.
Abstract: Background: Esthesioneuroblastoma (ENB) is a rare neuroendocrine tumor. The purpose of this study was to compare the Kadish, tumor‐node‐metastasis (TNM), and Dulguerov's modified TNM staging in order to determine the impact of the stage on primary surgical treatment selection, margin status, and survival. Methods: The National Cancer Database (NCDB) was used to identify patients diagnosed with ENB between 2004 to 2015. Patients were excluded based on the ability to properly stage their disease as well as the availability of treatment data. Results: Eight‐hundred eighty‐three patients had sufficient data for analysis. On multivariate analysis, age and government insurance were associated with primary surgical treatment, whereas tumor stage, gender, race, hospital type and volume, and comorbidity score were not. Age, charlson‐deyo comorbidity (CDCC) score, hospital volume, and nodal status were found to be predictors of survival. Multivariate‐analysis controlling for stage failed to demonstrate clear survival differences between staging in both TNM and Kadish systems. T‐stage and the presence of regional nodal metastasis were associated with an increased risk of positive margins on multivariate analysis. Conclusion: Although primary surgical management and positive margins can be predicted by certain patient and tumor factors, clinical staging systems for ENB poorly predict prognosis over a 10‐year horizon.